Gladius Gallicus: Wybrane zagadnienia - Szubelak, Bronisław (Instytut Historyczny Uniwersytetu Wrocławskiego, 2023)
The cultural successors to Hallstaat was La Tene. Long iron La Tene swords were used from the beginning of the fifth to the end of the first century BC, at first designed mainly for thrusting, but later shaped as slashing weapons. Celtic swords had elaborately shaped anthropo-morphic or antennae hilts in bronze. However, blades from the La Tene period were made exclusively from iron.At first the form of the hilt was shaped like a human figure, the grip being the body within the outstretched arms and legs, and the head forming the pommel. More specifically, they were made in one of two ways – once the basic shape had been forged from a bar of iron, the edges were hardened by cold hammering, or the sword was constructed by joining strips of iron with different carbon content under heat so that it was, in effect, steeledged. La Tene swords had straight, parallel-sided blades, although some steel carried a long itudinal rib like bronze swords, with narrow tangs. Towards the end of period, Celtic swords on the continent began to favour rounded points, though many contemporary swords found in Britain remain acutely pointed. British swords tended to be a little shorter and thinner than continental ones. The thinner and shorter swords might have beeninfantry weapons, more useful for face-to-face combat. A long sword with its rounded tip would have allowedthe riders to slash at his enemies. Together with the weight of the weapon itself, such a blow was capableof cutting through the shield, armour and bone. With improvements in ironworking techniques and the evolutionof fighting styles the increasing role of cavalry, longer blades become more common in the last two centuries BC. The Celtic long sword came to symbolize the high status warrior.
Keywords: długi miecz; klinga (głownia miecza); damast skuwany; sztycharz; pochwa